Charm offensive : commodifying femininity in postwar France - Colvin, Kelly Ricciardi (University of Toronto Press, 2023)
"In the aftermath of the Second World War, the French government cultivated images of sensual and sophisticated white French women in an attempt to reestablish its global image as a great nation. French publicists, journalists, and government officials working in the tourism industry began a concerted effort to improve France's international image and win valuable tourist money by promoting the beauty, sexual appeal, and general allure of French women, all while shrinking the boundaries of what was considered beautiful. Charm Offensive explores how this elevation of French femininity created problems on both sides of the equation: the pressure on French women to conform to an exacting physical standard was immense, while the inability of anyone else to access that standard, coupled with the constant prods to try, resulted in a sense of failure. Drawing on cultural figures like Air France air hostesses, tourism workers, and celebrities such as Brigitte Bardot, the book demonstrates how women were mobilized as ambassadors of French superiority. Analysing cultural and political sources simultaneously, Charm Offensive offers an innovative understanding of a tumultuous time of decolonization."--